The Dual Role of Islamic Religious Education Teachers as Counselors in the Ili Olong Ea Laleng Area, Omeuri Sub-District - Baharudin Bapa; Tobroni; Nurul Humaidi (Didaktika: Jurnal Kependidikan, 2024)
This study examines the dual role of Islamic Religious Education (PAI) teachers, such as Jou, in the Ili Olong Ea Laleng area, Omeuri District. Jou, in this context, refers to a community spiritual teacher who is respected and has an essential role in shaping the morals and spirituality of the local community. PAI teachers function not only as teachers but also as role models and liaisons between the school and the community, as well as guardians of local Islamic traditions. The research method used was qualitative with a case study approach, in which data were collected through observation, in-depth interviews, and documentation to gain a comprehensive understanding of the roles and responsibilities of PAI teachers in community life. The research subjects involved PAI teachers, students, and community leaders who have a dPAIct relationship with the role of PAI teachers as Jou. The findings showed that the dual role of PAI teachers includes several main aspects, namely as educators, moral builders, spiritual leaders, motivators, and guardians of Islamic traditions. This study's results show that the PAI teachers' role, as Jou, is crucial in strengthening religious and moral values in the community and maintaining social harmony in the region. This research is expected to contribute to the development of religious education in the community and strengthen the role of teachers in fostering the morals of the younger generation.